Faces da fronteira: a atuação indígena na criação de missões no vale do rio Oiapoque (1729-1765) - Karolliny Diniz; Sidney Lobato (Caravelle)
This article aims to analyze the indigenous people participation in the creation of French religious missions in the Oyapock River valley, between 1729 and 1765. The research was based on edifying and curious letters written by Jesuits. We infer that the Native Americans participated in the definition of the places where the missions were installed and chose the people to be gathered there. As catechists, they also became important agents of christianization.